ACADEMIC AFFAIRS OPERATIONS OF SCHOOLS UNDER NAKHON SI THAMMARAT PRIMARY EDUCATIONAL SERVICE AREA OFFICE 3 - Thammachart, Paitong; Taneerat, Boonlert (Journal of MCU Nakhondhat, 2025)
This research aimed to investigate the academic affairs operations of schools as perceived by teachers, to compare the academic affairs operations of schools as perceived by teachers in relevance to their gender, educational level, academic standing, work experience, school size, administrators’ gender, and academic standing, and to examine problems and suggestions concerning academic affairs operations of schools. This research study uses a survey research method. The population is 1,515 teachers under Nakhon Si Thammarat Primary Educational Service Area Office 3. The sample consisted of 287 teachers, followed by proportional stratified random sampling based on school size. The data collection instrument was a five-point rating scale questionnaire with a consistency index ranging between .80 - 1.00 and an overall reliability coefficient of .986. The data analysis statistics comprised percentage, mean, standard deviation, One-way ANOVA, and LSD test. The findings revealed that 1) The schools’ overall academic affairs operations as perceived by teachers were found at good levels ( = 4.43, S.D. = 0.40). 2) There were no differences in the overall comparison results of the schools’ academic affairs operations as perceived by teachers in relevance to their gender, educational level, and administrators’ academic standing. However, there were significant differences found between academic standings and school sizes at .05 level, work experiences at .01 level, and administrators’ genders at .001 level. and 3) Problems indicated that some administrators lacked expertise in curriculum development, learning process development and internal quality assurance system development.